2019
DOI: 10.3390/rs11101150
|View full text |Cite
|
Sign up to set email alerts
|

Fitted PROSAIL Parameterization of Leaf Inclinations, Water Content and Brown Pigment Content for Winter Wheat and Maize Canopies

Abstract: Decades after release of the first PROSPECT + SAIL (commonly called PROSAIL) versions, the model is still the most famous representative in the field of canopy reflectance modelling and has been widely used to obtain plant biochemical and structural variables, particularly in the agricultural context. The performance of the retrieval is usually assessed by quantifying the distance between the estimated and the in situ measured variables. While this has worked for hundreds of studies that obtained canopy densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 109 publications
10
54
0
Order By: Relevance
“…In this study, the PROSAIL RTM [52] was used to assess the influence of leaf and canopy PTs on the SVIs calculated based on VIS, RE and NIR-shoulder spectral regions. PROSAIL couples two separate models: (a) the PROSPECT leaf optical model; and (b) the SAIL canopy reflectance model [28]. PROSAIL can simulate the canopy bidirectional reflectance in the spectral range between 400 and 2500 nm as a function of up to 16 input parameters.…”
Section: Svis Performance Using Simulated Spectra Under Different Temmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the PROSAIL RTM [52] was used to assess the influence of leaf and canopy PTs on the SVIs calculated based on VIS, RE and NIR-shoulder spectral regions. PROSAIL couples two separate models: (a) the PROSPECT leaf optical model; and (b) the SAIL canopy reflectance model [28]. PROSAIL can simulate the canopy bidirectional reflectance in the spectral range between 400 and 2500 nm as a function of up to 16 input parameters.…”
Section: Svis Performance Using Simulated Spectra Under Different Temmentioning
confidence: 99%
“…In addition, RTMs are mainly focused on chlorophyll and not on other pigments such as brown pigment content (polyphenols; Cbrown) which play an important role in shaping the spectral response of grasslands at varying phenological stages. This trait is rather poorly analyzed in the literature and the RTM parameter itself lacks of a proper physically meaning, and it is thus not measurable with field observations [28].…”
Section: Introductionmentioning
confidence: 99%
“…Since the parametrization of ProSAIL is crucial for the quality of the LAI derivation, in-situ values for the parametrization were used, which were obtained by Danner et al (2019) at the MNI testsite. A LUT for maize and a LUT for the two winter cereals (winter wheat and triticale) with 240,000 and 562,500 reference spectra, respectively, was created for each image acquisition date according to Table 2.…”
Section: Use Case For Demonstrating the Capacities Of The Solutionmentioning
confidence: 99%
“…In this study the parameters were obtained from in-situ measurements taken at the MNI test area. However, Danner et al (2019) found that the use of in-situ parameters in ProSAIL alone does not provide optimal results and manual adjustments are necessary to achieve higher retrieval accuracy. Since such a manual adjustments were omitted for reasons of time, there is further potential for error.…”
Section: Consistency Of In-situ and Satellite Datamentioning
confidence: 99%
See 1 more Smart Citation